Continuous Power Flow and Time Domain Analysis for Assessing Voltage Stability - Wiwin Armoldo Oktaviani; Taufik Barlian; Yosi Apriani; Nugraha Syarif (Journal of Robotics and Control (JRC), 2020)
Voltage instability is considered one of the primary sources of insecurity in power systems. Voltage instability is the phenomenon in which the voltage on the receiver's side is dropping far below the normal value and does not return even after establishing a voltage recovery mechanism, or continue to oscillate due to lack of attenuation. In this study, there will be a voltage stability analysis on the power system in several phases by conducting a power flow analysis, static voltage stability analysis using continuous power flow method, and dynamic voltage stability analysis using the time-domain analysis. The power system tested on this research is the IEEE 6 bus system from Wood Wollenberg, with the software used for the simulation, which is PSAT. The results show that voltage stability analysis using Continuous Power Flow and Time Domain Analysis can provide a more comprehensive overview of a power system stability level.  The highest decrease in voltage with a value of 1.5% appears in Bus 5 which is also suffering the lowest stability level. The system has a load margin (λ) value of 1.6130 a clearing time of under 0.4 seconds